Analisis Pelaksanaan Program Keselamatan Dan Kesehatan Kerja Dalam Upaya Meminimalkan Kecelakaan Kerja Pada Pegawai PT. Kereta Api Indonesia (Persero) : Studi kasus pada Depo Lokomotif Daop 2 Bandung PT. KAI - Heri Nugraha; Linda Yulia (Coopetition : Jurnal Ilmiah Manajemen, 2019)
The implementation of occupational safety and health carried out by all employees must be oriented to completion of work. This study was designed to describe work safety and work safety at PT. Indonesian Railways. Data collection techniques used in this research are conducting field studies by direct monitoring, interviews, and documentation. Analysis of the data used in this study is an interactive analysis that begins with data reduction, data presentation and conclusion conclusions obtained about the facts that occur in the field. Research results Obtained from that, the implementation of occupational safety and health programs at PT. Indonesian Railways was not carried out due to lack of facilities and the minimal number of participants participating in the training.